GeoGebra Research in Indonesia: A Bibliometric Analysis - Supriyadi, Edi; Septian, Ari; Dahlan, Jarnawi Afgani; Juandi, Dadang (PRISMA, 2022)
There is evidence that utilizing GeoGebra in the classroom can be beneficial, especially in the field of mathematics. Dynamic Geometry Software (DGS) such as GeoGebra is a category of a computer program that combines algebraic and geometric capabilities. In the beginning, GeoGebra was nothing more than an application that could be used on personal computers. Because bibliometric analysis is employed in GeoGebra research projects. In addition, the objective of this work is to undertake bibliometric analysis to determine the development of GeoGebra research in Indonesia. A bibliometric analysis was carried out with the intention of evaluating the previous work that has been done on the topic of GeoGebra in Indonesia. We are interested in examining the progression of GeoGebra research outcomes in Indonesia, as well as the distribution pattern of publications in Scopus. The results are displayed in a short amount of time and in certain cases provide a comprehensive look at the developments and standing of the GeoGebra literature by affiliation from Indonesia, including information on authors, institutions, nations, and author keywords. For the purpose of clarity, the author's own keywords are the only ones used in the data analysis in this study. However, no R programming language library currently exists that can handle this issue.